Guias Didáticos: Propostas Inovadoras II - Franciosi, Anelise; Yoshi, Cássia Valéria Hungaro; Gomes Junior, Estevão Conceição; Magalhães, Leandro Henrique; Bailoni, Ludmila Fratucci; Cavariani, Marilia Martins; Camargo Filho, Paulo Sérgio de (Livros Editora UniFil, 2024)
Acesse o e-book  aqui